Functional brain alterations in Cushing’s syndrome - Papakokkinou, Eleni; Ragnarsson, Oskar (Frontiers in Endocrinology, 2023)
Cognitive impairment and affective disorders are common in patients with Cushing’s syndrome (CS). In fact, as an effect of prolonged cortisol excess on the brain, patients with CS often have memory problems, concentration difficulties, impaired attention and executive function, that are not always reversible following successful treatment. Neuroimaging is essential for understanding the deleterious effects of hypercortisolism on the brain. In CS, structural alterations have been observed, including reduction of hippocampal volume, amygdala and the prefrontal cortex. The aim of this article is to summarize results from studies that have used functional magnetic resonance imaging (fMRI) to study functional brain alterations in patients with CS. In these studies, alterations in brain areas and networks essential for cognitive function, emotional processing, and executive function have been observed, both in patients with active CS as well as following treatment. Nevertheless, longitudinal studies with a comprehensive evaluation of functional brain alterations and neurocognitive evaluation are still needed to determine whether the apparent deleterious effects of hypercortisolism on the brain are reversible or not.